2021
DOI: 10.5489/cuaj.7066
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune memory is associated with increased disease-free survival in bladder cancer patients treated with bacillus Calmette-Guérin

Abstract: Introduction: While studies suggest that innate immune memory acquired by circulating monocytes may mediate the benefit of bacillus Calmette-Guérin (BCG) in the treatment of patients with high-risk non-muscle-invasive bladder cancer (NMIBC), prospective studies are lacking. Innate immune memory is defined by enhanced release of pro-inflammatory cytokines by innate immune cells following a secondary challenge with pattern recognition receptor (PRR) ligands. Methods: Peripheral blood monocytes isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“… 46 Graham et al described variable post-BCG versus pre-BCG ratios of cytokines released by monocytes following LPS stimulation in 33 NMIBC patients during BCG induction, with approximately half of the patients showing an increase in ratios. 95 A limitation of all these studies is that they only assessed the cytokine production during a BCG induction cycle which may be influenced by the immunological processes of priming or tolerance. 68 …”
Section: Discussionmentioning
confidence: 99%
“… 46 Graham et al described variable post-BCG versus pre-BCG ratios of cytokines released by monocytes following LPS stimulation in 33 NMIBC patients during BCG induction, with approximately half of the patients showing an increase in ratios. 95 A limitation of all these studies is that they only assessed the cytokine production during a BCG induction cycle which may be influenced by the immunological processes of priming or tolerance. 68 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that tumor immune environments may interact with BCG and interfere with the efficacy of this therapy. For instance, IL-12 secreted by BCG-induced monocytes was increased in NMIBC patients without tumor recurrence, a phenomenon that may involve the innate immune memory of circulating monocytes [ 45 ]. Nevertheless, patients receiving BCG in our study did not have peripheral immune cell profiles that differed from patients who were BCG naïve, and BCG was not significantly associated with NMIBC outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes isolated from patients with bladder cancer after intravesical BCG demonstrated enhanced cytokine responses to ex vivo stimulation with lipopolysaccharide (LPS) compared to monocytes from the same patients before BCG treatment was initiated, suggesting that these monocytes had undergone immune training [67]. Furthermore, increased secretion of IL-12 by monocytes stimulated ex vivo with LPS after completion of five weekly instillations of BCG as compared to before BCG initiation was found to correlate with favorable clinical responses [68]. Further studies are ongoing to clarify the role of trained immunity in BCG treatment of bladder cancer.…”
Section: Trained Immunitymentioning
confidence: 99%